114 THE UNMANNED AIRCRAFT CAPABILITIES IN INTEGRATED MARITIME DEFENSE TO SUPPORT WORLD MARITIME AXIS POLICY - Yulmaizir Chaniago; Yusnaldi Yusnaldi (Strategi Pertahanan Udara, 2022)
Indonesian National Armed Forces, the Air Force, as a means of national defense , had the task of upholding the sovereignty of the unitary state of the Republic of Indonesia and the territorial integrity of country, especially in the context of upholding state sovereignty in the air, and supporting the enforcement of state sovereignty on land and at sea. In order to realize this, the Indonesian Air Force through one of its functions in its territorial development is through fostering the potential of aerospace, through the empowerment of defense areas. The development of aerospace potential is carried out as an effort to realize the creation of regional security around the base. This research method is a qualitative method with observation techniques, documentation studies and interviews. The results of the study showed that there are still a level of vulnerability of security in around Atang Senjaya Air Force Base area which is the concentration of local security forces, office complexes, personnel and facilities and infrastructure that require a fairly high level of supervision. The existence of military installations, whether complex or office buildings, is still quite open and easily accessible to parties with certain interests. It is very important to establish a condition of the expected defense area through the synergy of all territorial apparatus in optimally carrying out the development of aerospace potential in the community, through the role of Binpotdirga personnel, in providing guidance, conducting effective communication, and participation from local government.Keywords: Air base, empowerment, regional defense , universal defense system, Atang Sendjaja